Integrating mental and behavioral health providers into VHA pain management teams and oncology clinics: assessment of early implementation from site visits - Molly Goodrich; Benjamin R. Szymanski; Brittany L. Cornwell; Kristen Perry; Katherine M. Dollar; Jennifer Patterson; John F. McCarthy (Frontiers in Health Services, 2026)
Introduction To enhance mental health access and suicide prevention services for Veteran patients in Pain Management Teams and Oncology Clinics, the Veterans Health Administration (VHA) initiated the Mental and Behavioral Health Integration (MBHI) Demonstration Projects at 53 facilities in 2022. MBHI integrates colocated mental health providers into these settings to deliver brief mental/behavioral healthcare. Findings describe site visits assessing early implementation. Methods Evaluators visited nine VHA facilities where MBHI providers were recruited and implementation was at early stages. Visits included program overviews, tours, and provider and site leadership interviews. Visits had consistent agendas and a framework of questions assessing fidelity to core components, site-specific modifications, and patients and conditions treated. Observations were content coded and organized thematically. Results and Discussion MBHI services were available at each facility. Sites varied regarding clinic space for MBHI, brief treatment model use, and MBHI same-day access availability. All sites reported positive impacts for Veterans, clinical operations, and facilities. Implementation strengths and facilitators included local buy-in, MBHI provider integration into teams, utilizing partnerships and resources, MBHI provider experience and approach to care, and clinic workflow. Implementation challenges included space limitations, competing MBHI provider demands, productivity demands, uncertainty about intended patient populations, difficulty integrating MBHI staff, and hiring challenges and specialty clinic nascency. Visits identified positive impacts of MBHI, facilitators, and barriers to program implementation. Information gathered from site visits can inform VA policies and operations. Results continue to inform program modifications including enhancing role clarity, medical provider buy-in, and ongoing competency training.